Postmodernity: "everything counts", useless as it may be - Saldaña, Alfredo (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
The contraversy about the crisis of modernity and the arrival of postmodernity has exceeded the realms of aesthetics and artistic creation to include the contribution of many a specialist from the social sciences, mainly in the last thirty years. This debate is to a great extent the aftermath of the breakdown of the concept of reason modernity entertained, a concept which helped to provide both the process or reality construction and the project of social emancipation attempted by modernity with coherence. The postmodern experience has rendered modern reason incapable of providing answers as to how to live together in a world pervaded by technology and irrationality, where economic relations and the media have taken over the privileged position once occupied by reason. As a reaction to the totalising and presumably liberating discourses elaborated by modernity some artists and theoretists have adopted a new stance. They outline a possible escape from the scepticism of postmodernity in their resistance to offer us their critical, alternative discourses, designed outside the boundaries of prevailing canons.
Keywords: Postmodernity; modernity